Empowering Farming Communities through the Application of Appropriate Technology in the Rice Polishing Machine in Koto Padang Village Dharmasraya Regency - Ardi, Junil; Fernandes, Erik; Irzal, Irzal; Primawati, Primawati; Dasa Putri, Lili (Universitas Negeri Padang, 2026)
This community service program aims to empower rice farmers in Koto Padang Village, Dharmasraya Regency, through the application of appropriate technology in the form of a rice polishing machine (polisher). The main problems faced by farmers were the absence of local polishing facilities and dependence on rice milling units in neighboring villages, which increased transportation costs, processing time, and reduced product quality. The implementation method used a participatory technology approach involving lecturers, students, and the Rawang Bintungan Farmers Group. The activity consisted of several stages: field survey, problem identification, machine design using SolidWorks, fabrication, testing, training, and handover. The machine, driven by a 7 HP motor, has a working capacity of 300–500 kg/hour with 90–95% milling efficiency. Results show that the machine reduced operating costs by up to 30% and increased rice yield quality and polishing efficiency compared to traditional methods. Furthermore, 90% of the trained participants were able to operate and maintain the machine independently. This program demonstrates that collaborative innovation between universities and local communities can strengthen food security and farmer independence through sustainable technology transfer.